2020
DOI: 10.1136/jitc-2019-000261
|View full text |Cite
|
Sign up to set email alerts
|

Late cardiac adverse events in patients with cancer treated with immune checkpoint inhibitors

Abstract: BackgroundImmune checkpoint inhibitor (ICI)-associated early cardiac adverse events (CAEs), mostly acute and fulminant myocarditis, have been well characterized and mainly occur during the first 90 days after ICI therapy initiation. ICI-associated late CAEs (occurring after the first 90 days of treatment) have not yet been described.MethodsFirst, we compared characteristics of a cohort involving early (defined as a CAE time to onset (TTO) of <90 days after ICI therapy initiation) and late (defined as a CAE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 21 publications
2
36
0
4
Order By: Relevance
“…Disproportionality analysis stated but not shown Moslehi et al (2018); Vigibase [ 35 ] Myocarditis 46% (higher in combo vs. monotherapies) Median TTO = 27 (data for 33 patients) 101 cases (57% with anti-PD-1). Concurrent irAEs in 42% (myositis, myasthenia gravis) Dolladille et al (2020); Vigibase [ 52 ] Cardiac events 30–27% (early and late events) Median TTO = 21 (early cases)—178 (late cases) for Vigibase; median TTO = 14 (early cases)—104 (late cases) in three French cardio-oncology units 437 early cases (onset < 90 days), 159 late cases (onset ≥ 90 cases); almost exclusively with anti-PD-1/PD-L1. Late cases had significantly more frequent HF (21.1% vs. 31.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Disproportionality analysis stated but not shown Moslehi et al (2018); Vigibase [ 35 ] Myocarditis 46% (higher in combo vs. monotherapies) Median TTO = 27 (data for 33 patients) 101 cases (57% with anti-PD-1). Concurrent irAEs in 42% (myositis, myasthenia gravis) Dolladille et al (2020); Vigibase [ 52 ] Cardiac events 30–27% (early and late events) Median TTO = 21 (early cases)—178 (late cases) for Vigibase; median TTO = 14 (early cases)—104 (late cases) in three French cardio-oncology units 437 early cases (onset < 90 days), 159 late cases (onset ≥ 90 cases); almost exclusively with anti-PD-1/PD-L1. Late cases had significantly more frequent HF (21.1% vs. 31.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Seeing the high mortality rates of nearly 50%, the baseline value and continuous cTn monitoring throughout the cancer treatment become even more crucial [50]. Furthermore, concerns have been raised about late IRCAE occurring 90 days after the start of ICI treatment [51]. Patients diagnosed with late IRCAE mostly show symptoms and signs of heart failure and not myocarditis.…”
Section: Cardiac Troponins Predictors Of Ctacmentioning
confidence: 99%
“… 97 Compared with ICI-mediated early immunomyocarditis (occurring in the first 90 days of treatment), ICI-mediated late immunomyocarditis (after the first 90 days of treatment) is more likely to develop heart failure. 98 Although the incidence of immunomyocarditis is not high, the mortality rate of immunomyocarditis is the highest of all ICI-mediated side effects. Wang et al retrospectively analyzed 613 cases of fatal ICI-mediated side effects reported from 2009 to 2018 and found that 333 cases were caused by anti-PD-1/PD-L1, and 27 patients (8%) died from immunomyocarditis.…”
Section: Clinical Characteristics and Therapeutic Implications Of Immunomyocarditismentioning
confidence: 99%